Palaeomagnetism of the Late Devonian-Early Carboniferous Achala Batholith, Córdoba, central Argentina: Implications for the apparent polar wander path of Gondwana - Geuna, Silvana Evangelina (2008)
The Achala Batholith (31°30′S, 64°45′W, Córdoba, Argentina) is a major magmatic complex of the Sierras Pampeanas, emplaced as a post-orogenic pluton in a metamorphic-plutonic basement. It is mainly a porphyritic to coarse-grained equigranular monzogranite, with crystallization age of ∼ 370 and cooling age of ∼ 340 Ma, presently exposed as asymmetric, eastward-tilted blocks. Forty-three sites were sampled in the Achala monzogranite. Overall, it is weakly magnetic, with a mean magnetic susceptibility of 15 × 10- 5 (SI). Twenty-two sites showed unstable magnetic behaviour. The remaining 21 sites have haematite as magnetic carrier of a stable remanence. The ilmeno-haematite appears as an accessory mineral, with exsolved intergrowths of (haemo)ilmenite. Thermal demagnetisation up to 620-640 °C isolated steeply-dipping, dual-polarity remanence directions. The palaeomagnetic pole is located at 56°S, 307°E (N = 18, A95 10.7, K 11). The remanence was locked on cooling, over a range of temperatures from magnetic ordering to exsolution of ilmenite-haematite (∼ 600 to 390 °C). The pole better coincides with the 370-360 Ma segment of the Gondwana apparent polar wander path, suggesting that remanence was acquired quickly. The Achala pole matches a complex mid-Palaeozoic apparent polar wander path ("Y-type") for Gondwana, which may involve rapid movement, true polar wander episodes and/or continental collisions before the final amalgamation of Pangea.